Psychological Characteristics Of Primary School Students - Fayziyeva Nodira Sobirovna (Academia One, 2024)
In this article, the psychological characteristics of students of junior school age, the abilities found in them, how to determine the child's ability, why it is important to learn the child's ability early
Keywords: junior school age; ability; psychology; attitude